The reformed vampire support group - Jinks, Catherine 1963- (Houghton Mifflin Harcourt, 2009)
Fifteen-year-old vampire Nina has been stuck for fifty-one years in a boring support group for vampires, and nothing exciting has ever happened to them--until one of them is murdered and the others must try to solve the crime.